The Commercial Aircraft Finance Handbook - Scheinberg, Ronald (London : Taylor and Francis, 2017)
"The Commercial Aircraft Finance Handbook is a resource for every type of aircraft finance practitioner - seasoned and starter alike. The handbook offers a comprehensive overview of the multifaceted matters that arise in the process of financing commercial aircraft. The book clearly reviews the different topics on a high-level basis, and then explains the terminology used for each particular area of specialization. It can be used as both a learning aid and reference resource. The area of commercial aircraft finance is multidisciplinary one, touching professionals across law, finance, insurance, and leasing (to name a few) and this book arms these diverse practitioners with a framework for knowing the questions and issues that should be considered in an aircraft financing transaction. This book will also provide practitioners just starting out in this field with an introduction to the myriad of topics in aircraft finance while providing more seasoned professionals with explanations of matters outside their normal area of expertise. As well, all practitioners will benefit from the resources provided in the appendices."--Provided by publisher.
Keywords: Aeronautics, Commercial -- Finance; Aircraft industry -- Finance; Aeronautics, Commercial -- Law and legislation; Aerospace & Air Transport Industries; Aerospace & Aviation Engineering; Aerospace Engineering; Aviation Manufacturing Industry; Banking and Finance Law for Professionals; International Business; Strategic Management